Other resonances and ontologies: thinking with the Bantu-Kongo thinking - Santos, Tiganá Santana Neves (2022)
In light of fundamental aspects of Bantu-Kongo thinking and in line with contemporary thinkers, such as Bunseki Fu-Kiau and Zamenga B., this article aims to reflect on ontologies distinct from those of Euro-Western hegemony. Such ontologies are experienced in part of the African continent and have been moved to Afrodiasporic territories, such as Brazil, although with adaptations, through cosmological practices that situate ancestry in a central place. The ideas of “pluriontological sameness” (as we coin with a hermeneutic basis in Kongo philosophy), opacity (from Édouard Glissant's theoretical suggestion), stages of the Kongo cosmogram, emptiness, transmutation, inclination towards otherness, science of sorcery, system, ecological entities, inter-actions propose complex possibilities of being-living, in relation, which are radically far from metaphysics and ethics developed in the heart of Western thinking, as well as can dialogue with them, which makes us, by thinking on the side of the Afrodiasporic margin of the Atlantic, consider the tensions between these different ways of thinking that occupy asymmetric spaces in historical constructs.